Prediction of improved antimalarial chemoprevention with weekly dosing of dihydroartemisinin-piperaquine. - Permala, J; Tarning, J; Nosten, F; White, N; Karlsson, M; Bergstrand, M (American Society for Microbiology, 2017)
Intermittent preventive treatment (IPT) is used to reduce malaria morbidity and mortality, especially in vulnerable groups such as children and pregnant women. IPT with the fixed dose combination of piperaquine (PQ) and dihydroartemisinin (DHA) is being evaluated as a potential mass treatment to control and eliminate artemisinin resistant falciparum malaria. This study explored alternative DHA-PQ adult dosing regimens compared to the monthly adult dosing regimen currently being studied in clinical trials. A time-to-event model describing the concentration-effect relationship of preventive DHA-PQ administration was used to explore the potential clinical efficacy of once weekly adult dosing regimens. Loading dose strategies were evaluated and the advantage of weekly dosing regimen was tested against different degrees of adherence. Assuming perfect adherence, three tablets weekly dosing regimen scenarios maintained malaria incidence of 0.2-0.3% per year, compared to 2.1-2.6% for all monthly dosing regimen scenarios and 52% for placebo. The three tablets weekly dosing regimen was also more forgiving (i.e. less sensitive to poor adherence), resulting in a predicted ∼4% malaria incidence per year compared to ∼8% for dosing regimen of two tablets weekly and ∼10% for monthly regimens (assuming 60% adherence and 35% inter-individual variability). These results suggest that weekly dosing of DHA-PQ for malaria chemoprevention would improve treatment outcomes compared to monthly administration by lowering the incidence of malaria infections, reducing safety concerns about high PQ peak plasma concentrations and being more forgiving. In addition, weekly dosing is expected to reduce the selection pressure for PQ resistance.